2005
DOI: 10.1111/j.1528-1167.2005.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Outcome in Psychogenic Nonepileptic Seizures: How Relevant Is Seizure Remission?

Abstract: Summary:  Purpose: To examine whether seizure remission is a comprehensive marker of outcome in psychogenic nonepileptic seizures (PNESs). Methods: A postal questionnaire was returned by 147 patients with PNESs a mean of 4.2 years after diagnosis (mean age at follow‐up, 38.1 years). The proportion of patients who were “unproductive” (receiving health‐related state benefits) at follow‐up was determined, with a comparison of markers of ongoing psychopathology (Global Severity Index, anxiety and depression score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 56 publications
5
75
0
1
Order By: Relevance
“…For example, in one study, nearly half of the patients remained disabled because of psychiatric symptoms even though they no longer had PNES. 10 Depression contributes to poor QOL in patients with PNES and ES. In patients with epilepsy, depression symptomology is a strong predictor of a worse QOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in one study, nearly half of the patients remained disabled because of psychiatric symptoms even though they no longer had PNES. 10 Depression contributes to poor QOL in patients with PNES and ES. In patients with epilepsy, depression symptomology is a strong predictor of a worse QOL.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have suggested seizure remission alone may not be an adequate outcome in PNES studies, as patients with reduced seizures may continue to have psychiatric symptoms and remain disabled. 10 The relationship between seizure frequency and quality of life (QOL) has been studied in patients with epilepsy, but not as extensively in patients with PNES. Gilliam 11 studied 195 patients with epilepsy to determine the relationship of neuropsychiatric function and QOL.…”
mentioning
confidence: 99%
“…According to Reuber et al [1] Psychogenic no epileptic seizures (PNES) can be defined as a form of paroxysmal behavior that mimics epileptic seizures and is characterized by a sudden and time-limited disturbance of motor, sensory, autonomic, cognitive and emotional functions, or a combination of these. However, the main feature is that these epileptic-like seizures are displayed without an abnormal Electroencephalographic (EEG) activity.…”
Section: Introductionmentioning
confidence: 99%
“…While short-term seizure cessation cannot be the only treatment goal in this patient group [35], it is clearly relevant and was achieved in one third of patients.…”
Section: Discussionmentioning
confidence: 99%